Natural Area Weeds: Mexican Petunia (Ruellia tweediana) - Karen V. S. Hupp; Alison M. Fox; Sandra B. Wilson; Emily L. Barnett; Randall K. Stocker (EDIS)
ENH1155, an 8-page illustrated fact sheet by Karen V. S. Hupp, Alison M. Fox, Sandra B. Wilson, Emily L. Barnett, and Randall K. Stocker, describes this herbaceous perennial that is popular with consumers, landscapers, and growers — its preferred habitat, dispersal, hybridization, cultivars, invasive status and distribution in natural areas, IFAS Assessment, and control. Includes references. Published by the UF Department of Environmental Horticulture, December 2009.